ANALISIS BIBLIOMETRIK ATAS PENDETEKSIAN FRAUD MENGGUNAKAN APLIKASI VOSVIEWER: ANALISIS BIBLIOMETRIK ATAS PENDETEKSIAN FRAUD MENGGUNAKAN APLIKASI VOSVIEWER - Muhamad Teguh Satria (ECO-BUILD, 2025)
This study aims to further discuss the deepening of the concept of fraud detection and provide greater insight into the concept of fraud detection. Data sources were collected from the Scopus database as many as 200 documents from 2010 to 2023. This research method uses bibliometric analysis with an application system for data visualization using VOSviewer. Enrichment of information based on scientific data regarding the phenomenon of fraud detection and handling is an interesting and useful thing to continue to be researched. Differences in location, situation and time make the dynamics of fraud detection efforts more effective and have a positive impact theoretically and in practice. This research can be a reference for future researchers in conducting scientific studies on improving the concept of fraud detection. This research provides new insights through the elaboration of information data regarding the concept of implementing fraud detection so that it can be useful in evaluating the company's internal control.